2020
DOI: 10.21203/rs.3.rs-93711/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical impact of confinement due to the COVID-19 pandemic on patients with fibromyalgia: A cohort study

Abstract: Background: Data on the effect of the COVID-19 pandemic on fibromyalgia (FM) patients are lacking. FM patients often experience clinical impairment with stress situations.The objective of this study was to determine whether severity of FM increases because of confinement due to the COVID-19 pandemic.Methods: Prospective study including patients from the Combined Index of Severity of Fibromyalgia (ICAF) cohort who met the 2010 ACR FM criteria. In this cohort, all patients have a periodical evaluation of their q… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Importantly, four studies highlighted the importance of positive coping strategies, including regular physical exercise, positive reappraisal, refocusing, and planning, and a high ability to self-manage pain. These coping methods helped mitigate the pandemic's impact on disease management, leading to an increase in wellbeing outcomes related to pain, sleep, anxiety, and depression [36,39,41,47]. In another study showing symptom improvements in fibromyalgia patients, authors suggested that positive outcomes were attributable to reduced social constraints and work pressure [38].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Importantly, four studies highlighted the importance of positive coping strategies, including regular physical exercise, positive reappraisal, refocusing, and planning, and a high ability to self-manage pain. These coping methods helped mitigate the pandemic's impact on disease management, leading to an increase in wellbeing outcomes related to pain, sleep, anxiety, and depression [36,39,41,47]. In another study showing symptom improvements in fibromyalgia patients, authors suggested that positive outcomes were attributable to reduced social constraints and work pressure [38].…”
Section: Discussionmentioning
confidence: 99%
“…Despite four of the seven studies finding worsened clinical outcomes, three studies from Europe found no changes or slight improvements in fibromyalgia patient outcomes during the pandemic [36,38,39]. Within these studies, positive outcomes were mostly attributed to effective patients' coping skills [39] and their adaptability, including positive reappraisal and refocusing [36].…”
Section: Fibromyalgiamentioning
confidence: 95%
See 2 more Smart Citations